A new dieback disease of the forage legume Stylosanthes guianensis in South America - Kelemu, Segenet; Badel, JL; Fernandes, C.D. (Informa UK Limited, 1997)
A wilt and eventual dieback disease ot the forage legume Stylosanthes guianens which occurs widely in Colombia and Brazil, is described. The causal agent of the wilt disease is identified as Lasiodiplodia theobromae, a virulent, unspeciaIized, facultative, wound pathogen with worldwide distribution and more than 500 different host plants. The 1-septate conidia are slow maturing, brown, thick walled, and striate. Genotypes of S. guianensis vary in their reactions to the pathogen. Of eight important S. guianensis genotypes tested for their reaction to the pathogen, the Brazilian cultivar Mineirao was the most susceptible, and CIAT 10136 and FM 9405 parcela Y were the most resistant.